Common features of Budd Chiari syndrome in Sudanese population: a computed tomography-based review and descriptive analysis - Ali Bakry, Abdoelrahman Hassan; Bashir, Auis; Almuqbil, Nora; Alamin, Asma; Fadulelmulla, Ibtisam Abdallah; ALMansour, Abdullah G. M.; Omer, Awatif M.; Bairam, Hozaifa Hassan; Sulieman, Abdelmoneim; Hamd, Zuhal Y. (Frontiers in Medicine, 2025)
PurposeDifferent hospitals in Sudan detected a rare condition of liver vascular abnormalities characterized by vascular outflow impairment. The study aimed to describe the common radiological features of Budd Chiari syndrome and determine which feature is most frequently employed to characterize this condition during imaging techniques, primarily contrast-enhanced computed tomography (CECT) scans.Materials and methodsThe study was conducted between March 2023 and June 2024 at Kuwaiti Specialized Hospital (KSH) and other diagnostic centers using a liver protocol on a CT machine (Optima 520 GE-CT machine, 16 slices). The study was a retrospective, cross-sectional, and review-based analysis of a rare study type carried out to characterize the state of BCS in Sudan; the CT scan’s findings on the liver, HVs, IVC, and abdomen were carefully assessed. The age range of the 61 patients who underwent a successful triphasic CT abdomen for the liver was 2–78 years.ResultsThe findings indicate that: the majority of patients 57.4% were male, the most common age groups were 39–52 years old, and the mean age at diagnosis was 45 years. BCS is primarily caused by hepatic veins (HVs) thrombosis, which is observed in 18.03% of cases, and HVs are not seen in 55.73% of cases. Liver parenchymal enhancement appears heterogenous in 27.87%, while heterogeneously enlarged liver was seen in 24.59%, and cirrhotic in 14.75% of BCS patients. In comparison, 59.01 percent of BCS patients arrived without varices. Varices were observed in the splenorenal and gastroesophageal regions in 37.7% of cases. Ascites accounted for the majority of BCS complications 73.77%, with SM vein blockage and squeezed duodenum accounting for 3.27% of each complication. The likelihood of developing ascites increases with age, and it is most common in patients between the ages of 39 and 52 years. Patient age had the greatest effect on the development of ascites.ConclusionThe common features of BCS as revealed by contrast-enhanced CT of the liver are non-visible HVs, venous occlusion at either level of HVs or IVC, caudate lobe enlargement, heterogenous, normal or enlarged liver, collateral venous varices at the splenorenal and gastroesophageal region, and ascites.